Fas regulates neutrophil lifespan during viral and bacterial infection. Issue 2 (3rd December 2014) - O'Donnell, Joanne A.; Kennedy, Catherine L.; Pellegrini, Marc; Nowell, Cameron J.; Zhang, Jian‐Guo; O'Reilly, Lorraine A.; Cengia, Louise; Dias, Stuart; Masters, Seth L.; Hartland, Elizabeth L.; Roberts, Andrew W.; Gerlic, Motti; et al.
Abstract : Neutrophils use Toll‐like receptor and IL‐18 signaling to reprogram Fas‐induced death. Abstract : The regulation of neutrophil lifespan is critical for a circumscribed immune response. Neutrophils are sensitive to Fas/CD95 death receptor signaling in vitro, but it is unknown if Fas regulates neutrophil lifespan in vivo. We hypothesized that FasL‐expressing CD8 + T cells, which kill antigen‐stimulated T cells during chronic viral infection, can also induce neutrophil death in tissues during infection. With the use of LysM‐Cre Fas fl/fl mice, which lack Fas expression in macrophages and neutrophils, we show that Fas regulates neutrophil lifespan during lymphocytic choriomeningitis virus (LCMV) infection in the lung, peripheral blood, and spleen. Fas also contributed to the regulation of neutrophil numbers in the colon of Citrobacter rodentium ‐infected mice. To examine the effects of infection on Fas activation in neutrophils, we primed neutrophils with TLR ligands or IL‐18, resulting in ablation of Fas death receptor signaling. These data provide the first in vivo genetic evidence that neutrophil lifespan is controlled by death receptor signaling and provide a mechanism to account for neutrophil resistance to Fas stimulation during infection.